2010
DOI: 10.1038/onc.2010.452
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of Wilms tumor-suppressor WTX and tumor-associated mutants

Abstract: The WTX, Wilms tumor-associated tumor-suppressor gene, is present on the X chromosome and a single WTX mutation may be sufficient to promote carcinogenesis. Unlike the WT1 tumor suppressor, a transcription factor, WTX lacks conserved functional protein domains. To study the function of WTX, we constructed inducible cell lines expressing WTX and tumor-associated WTX mutants. Induction of WTX inhibited cell growth and caused G 1 /G 0 arrest. In contrast, a short, tumorassociated truncation mutant of WTX358 only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…We hypothesize that WTX enhances NRF2 steady-state levels by disrupting the conformation of the E3 ubiquitin ligase complex, resulting in lower ubiquitination of NRF2. In support of our findings, expression of the NRF2 target genes NQO1 and HMOX1 was significantly enhanced in HEK293T cells overexpressing a fragment of WTX containing the KEAP1 interaction domain (37). …”
Section: Discussionsupporting
confidence: 83%
“…We hypothesize that WTX enhances NRF2 steady-state levels by disrupting the conformation of the E3 ubiquitin ligase complex, resulting in lower ubiquitination of NRF2. In support of our findings, expression of the NRF2 target genes NQO1 and HMOX1 was significantly enhanced in HEK293T cells overexpressing a fragment of WTX containing the KEAP1 interaction domain (37). …”
Section: Discussionsupporting
confidence: 83%
“…A lack of WT1 induces WT precursor cells to undergo apoptosis and mutant b-catenin might rescue the cells by the activation of Wnt signaling. (24) The present study showed the comparable frequencies of WTX abnormalities in sporadic WTs with and without WT1 abnormalities; the findings were previously reported by Ruteshouser et al (Table 2). (18) In addition to the inhibitory role in Wnt signaling pathway, WTX has another role in nuclear pathways implicated in the transcriptional regulation of cellular differentiation and cell death programs, (24,25) and the damage of this pathway by WTX alterations might involve in the tumorigenic process and explain why the alterations were found in both WT1-wild-type and WT1-mutant type tumors.…”
Section: Discussionsupporting
confidence: 80%
“…A 10-l sample was added to a disposable cell counting chamber slide and inserted into a Countess automated cell counter (Invitrogen). The cell viability and total cell numbers were recorded from six independent experiments, as described earlier (29).…”
Section: Methodsmentioning
confidence: 99%